2006
DOI: 10.1021/la0630110
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to Surface-Initiated Ring-Opening Metathesis Polymerization of Cyclooctadiene

Abstract: Surface-initiated ring-opening metathesis polymerization of cyclooctadiene (COD), a low ring-strain olefin, is reported for the first time. Polymerization was carried out in the vapor phase, which is advantageous compared to conventional solution methods in terms of minimizing chain transfer by reducing polymer chain mobility at the vapor/solid interface. Attachments of a norbornenylcontaining silane and a Grubbs catalyst to silicon substrates were carried out before samples were exposed to COD vapor. The thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Lerum et al and Feng et al demonstrated that ROMP of these two monomers was possible by vapor deposition on a previously activated surface. 154,155 The active surface was made by reacting G2 catalyst with a norbornene functionalized silicon surface. The monomer vapor reacted at the surface and the polymerization was followed by measuring the surface thickness.…”
Section: Polymerization Mediamentioning
confidence: 99%
“…Lerum et al and Feng et al demonstrated that ROMP of these two monomers was possible by vapor deposition on a previously activated surface. 154,155 The active surface was made by reacting G2 catalyst with a norbornene functionalized silicon surface. The monomer vapor reacted at the surface and the polymerization was followed by measuring the surface thickness.…”
Section: Polymerization Mediamentioning
confidence: 99%
“…Our group recently reported the SiROMP of cis , cis -cycloocta-1,5-diene (COD), affording polybutadiene (PBd) films with thicknesses up to ~40 nm 22. The polymerization of low ring-strain monomers such as COD is non-trivial due to the propensity of chain transfer during polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm a good coverage of the polymer film, one could observe the attenuation of XPS signals from the substrate. For instance, the disappearance of silicon peaks is usually observed after the surface-initiated polymerization on the silica surface [39,86].…”
Section: Chemical Structures and Compositionsmentioning
confidence: 99%
“…Therefore, the driving force of the polymerization reaction is weaker, and the competitive effect of chain transfer reactions becomes more significant. By using vapor-phase monomers, the rate of chain transfer is minimized due to reduced chain mobility at the vapor-solid interface [86,89], so the polymerization can proceed in the forward direction at a faster rate. Lerum et al reported that the critical strain energy required to render the polymerization reaction thermodynamically feasible using vapor-phase monomers is only 2.2 kcal/mol, while the required strain energy of solution-phase monomers is estimated to be 13.3 kcal/mol [18].…”
Section: Techniques For Performing Si-rompmentioning
confidence: 99%